KAJIAN PERANAN EKO-ENZYM TERHADAP KELESTARIAN EKOSISTEM AIR SUNGAI - Radja, Anselmus R.; Goda, Karina D.; Ngaku, Maria Alfonsa (Agros Journal of Agriculture Science, 2024)
Water can be polluted by various contaminants, including suspended solids, oil, heavy metals, detergents, dissolved solids, and so on. Therefore, water must go through a processing stage first before being used for certain purposes. An ecosystem is a level of organisms that is higher than a community, or is the unity of a community and its environment where interrelationships occur. In this case it does not only include a series of plant and animal species, but also all kinds of forms of matter that carry out cycles in the system as well as the energy that is the source of power. To obtain the energy and materials needed for life, all communities depend on the abiotic environment. To achieve the desired goals in accordance with the conditions and capabilities of existing resources, a water control plan requires a series of criteria and alternatives. Apart from that, cooperation from all parties in this matter (general public, industry and government) is very important. Eco-enzyme is a remediation agent that utilizes active enzymes and microorganisms produced during the fermentation process to degrade pollutants that are harmful to the environment.